Roles of exosomes and exosome-derived miRNAs in pulmonary fibrosis - Yang, Yongfeng; Huang, Hong; Li, Yi (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis is a chronic, progressive fibrosing interstitial lung disease of unknown etiology that leads rapidly to death. It is characterized by the replacement of healthy tissue through altered extracellular matrix and damage to the alveolar structure. New pharmacological treatments and biomarkers are needed for pulmonary fibrosis to ensure better outcomes and earlier diagnosis of patients. Exosomes are nanoscale vesicles released by nearly all cell types and play a central role as mediators of cell-to-cell communication. Moreover, exosomes are emerging as a crucial factor in antigen presentation, immune response, immunomodulation, inflammation, and cellular phenotypic transformation, and have also shown promising therapeutic potential in pulmonary fibrosis. This review summarizes current knowledge of exosomes that may promote pulmonary fibrosis and be utilized for diagnostics and prognostics. In addition, the utilization of exosomes and their cargo miRNAs as a novel therapeutic and their potential mechanism(s) are also discussed. The review aims to elucidate the role of exosomes in the pathogenesis of pulmonary fibrosis and pave the way for developing novel therapeutics for pulmonary fibrosis. Further in-depth research and clinical trials on this topic are encouraged in the future.